Evaluating the Effectiveness of Forming Enterprises Competitive Advantages - Irina SIDANICH; Anna ZAPLATYNSKA; Oleksandr POSTELZHUK; Larysa HARASHCHENKO; Bogdan OPALCHUK (Communications of International Proceedings, 2020)
It is proposed methodological approach to assessing the impact of the external environment on the implementation of this process, which is based on general and specific principles of the system, process, value-oriented approaches and involves the use of a sound system of indicators of factors characteristic of global, national, sectoral and regional levels and formal methods of valuation, which increases the objectivity and decisions validity level in the process of achieving and retaining competitive advantages of trade entities based on an integral approach to the formation of competitive advantages. It is made implementation of the proposed methodological instruments, which used the results of internal possibilities valuation, realized the influence valuation of external factors and  set a favorable factors impact of all given levels, as well as negative impact some of them.
Keywords: competitive advantage; internal possibilities; business processes; international trade; external factors.